To solve the system of equations using the substitution method, let's set the equations equal to each other. We have the two equations:
- \( y = x^2 - 4x + 8 \)
- \( y = 3x - 4 \)
Since both equations are set equal to \( y \), we can substitute the expression for \( y \) from the second equation into the first equation:
\[ 3x - 4 = x^2 - 4x + 8 \]
Now, we rearrange the equation to set it to zero:
\[ x^2 - 4x - 3x + 8 + 4 = 0 \] \[ x^2 - 7x + 12 = 0 \]
Next, we can factor the quadratic equation:
\[ (x - 3)(x - 4) = 0 \]
Setting each factor to zero gives us the solutions for \( x \):
- \( x - 3 = 0 \) → \( x = 3 \)
- \( x - 4 = 0 \) → \( x = 4 \)
Now, we can substitute these values back into one of the original equations to find the corresponding \( y \) values. Using the linear equation \( y = 3x - 4 \):
For \( x = 3 \): \[ y = 3(3) - 4 = 9 - 4 = 5 \]
For \( x = 4 \): \[ y = 3(4) - 4 = 12 - 4 = 8 \]
Thus, the solutions to the system are:
- \( (3, 5) \)
- \( (4, 8) \)
So the system of equations is solved using the substitution method by equating the two expressions for \( y \) and then solving for \( x \).